Pendidikan Agama pada SLB - Nurhattati Fuad (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2008)
The execution of specific education for children with special requirement emerges in various form, among others is Specific School/ Sekolah Luar Biasa (SLB). In this institute they get special study service for all lessons areas that usually are given in school in general, for example natural sciences, social science, language, mathematics, artistic, and religion. All the lessons are taught to children having special requirement so that they can develop various potencies of his self (physical, intellectual, emotion, social). Specially for education of religion, it has been done research which the result of fore part by this readers. The research did with survey method in seven provinces that focuses at institute aspect, teachers, teaching-learning process, construction, and evaluation.